A structural model to assess international visitors' perceptions about local foods in Tanzania. Issue 6 (3rd June 2017) - Mgonja, John T.; Backman, Kenneth F.; Backman, Sheila J.; Moore, DeWayne D.; Hallo, Jeffrey C.
ABSTRACT: Interest in the use of local food in tourism and hospitality is growing in both industry and academic circles. Most research on local food has focused on its potential to enhance local community development, while relatively little research has examined the way tourists perceive local foods in developing countries. This study applies image theory to evaluate perceptions of international tourists regarding local foods in Tanzania. Data were collected between June and August, 2014 using a survey method. The study population consisted of 520 international tourists departing from Kilimanjaro International Airport. Data were analyzed using structural equation modeling (SEM) with EQS 6.2. The results demonstrated that cognitive/perceptual and affective evaluations are two interdependent psychological constructs which, taken together, play a key role in understanding individuals' overall perception about local foods. The cognitive/perceptual evaluations formed by individuals as a result of accumulated knowledge and beliefs about local foods influence the way individuals perceive local foods. Likewise, the affective evaluations (feelings) about local foods significantly influenced individuals' overall perceptions about local foods. The results also show that many hotels where tourists stayed did not provide sufficient varieties of, or information about, local foods. Recommendations arising from the research relating to food policy and regulation are presented.